Virtual collaborative writing in the workplace computer-mediated communication technologies and processes - Hewett, Beth L.; Robidoux, Charlotte, 1965- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
"This book investigates the use of computer-mediated communication technologies and collaborative processes to facilitate effective interdependent collaboration in writing projects, especially in virtual workplace settings"--Provided by publisher.